Finland : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
The Selected Issues paper on Finland underlies public finances and structural reform. The structural reforms encompassing labor and product markets as well the pension system would substantially improve the outlook for fiscal sustainability. Reductions in labor and product market inefficiencies is estimated, on the basis of a staff computable general equilibrium model, to raise output and employment significantly while reducing the price level. Additional pension reforms could further increase employment, boost economic growth, and improve public finances, as could improved expenditure efficiency, thereby creating room for further reductions in labor income taxation.